Analisis dan Penerapan Algoritma Naïve Bayes untuk Klasifikasi Penyakit Gingivitis - Fadhillah, Muhammad; Sari, Herlina Latipa; Elfianty, Lena (LPPM UNIKA Santo Thomas Medan, 2023)
The aim of this research is to implement the Naïve Bayes algorithm for gingivitis classification at Dental Polyclinic, UPTD Pasar Ikan Health Center Bengkulu. The diagnosis of gingivitis is one of the diagnoses with severe conditions that are often complained at Dental Polyclinic, UPTD Pasar Ikan Health Center Bengkulu. However, the problem is that the services are still very limited because doctors are only on duty for 2 days a week. Therefore, a method is needed that is able to classify the risk level of various gingivitis diagnoses that occur at UPTD Pasar Ikan Health Center Bengkulu so that it can be immediately treated with appropriate action using Naïve Bayes method. From the results of tests carried out by Naïve Bayes method, it can be used as a solution for using this system. In its implementation, Naïve Bayes method can classify types of gingivitis at UPTD Pasar Ikan Health Center Bengkulu